Diagnosis of autoimmune pancreatitis - Matsubayashi, Hiroyuki (World J Gastroenterol, 2014)
Autoimmune pancreatitis (AIP) is a distinct form of chronic pancreatitis that is increasingly being reported. The presentation and clinical image findings of AIP sometimes resemble those of several pancreatic malignancies, but the therapeutic strategy differs appreciably. Therefore, accurate diagnosis is necessary for cases of AIP. To date, AIP is classified into two distinct subtypes from the viewpoints of etiology, serum markers, histology, other organ involvements, and frequency of relapse: type 1 is related to IgG4 (lymphoplasmacytic sclerosing pancreatitis) and type 2 is related to a granulocytic epithelial lesion (idiopathic duct-centric chronic pancreatitis). Both types of AIP are characterized by focal or diffuse pancreatic enlargement accompanied with a narrowing of the main pancreatic duct, and both show dramatic responses to corticosteroid. Unlike type 2, type 1 is characteristically associated with increasing levels of serum IgG4 and positive serum autoantibodies, abundant infiltration of IgG4-positive plasmacytes, frequent extrapancreatic lesions, and relapse. These findings have led several countries to propose diagnostic criteria for AIP, which consist of essentially similar diagnostic items; however, several differences exist for each country, mainly due to differences in the definition of AIP and the modalities used to diagnose this disease. An attempt to unite the diagnostic criteria worldwide was made with the publication in 2011 of the international consensus diagnostic criteria for AIP, established at the 2010 Congress of the International Association of Pancreatology (IAP).